1.3 μm Q-switched solid-state laser based on few-layer ReS2 saturable absorber. (January 2019) - Lin, Mingxi; Peng, Qianqian; Hou, Wei; Fan, Xiuwei; Liu, Jie
Highlights: A 1.3 μm Q-switched laser based on ReS2 saturable absorber was demonstrated. The performance of the passive Q-switching laser has been investigated. The average output power of 78 mW and the pulse width of 403 ns were obtained. Abstract: A novel two-dimensional saturable absorber, few-layered rhenium disulfide (ReS2 ), was prepared by liquid phase exfoliation method successfully. Moreover, for the first time, it was successfully employed in passively Q-switched bulk Nd:YAG lasers at 1.3 μm in this paper. The maximum average output power of 78 mW was obtained with the shortest pulse width of 403 ns and the repetition rate of 214 kHz, corresponding to single pulse energy and pulse peak power of 0.42 µJ and 0.9 W, respectively. The results indicate that ReS2 has the potential to be used for passive Q-switching laser generation at 1.3 μm wavelength.